Redesign Of Machine Layout Using Systematic Layout Planning Method: ENGLISH - Sucahyo, Dito Samudera; Rusindiyanto, Rusindiyanto (Journal La Multiapp, 2024)
Optimizing the production process is one of the things that needs to be considered in a factory. Machines play an important role in the production process because they function as the main tool in the production process. Rearrangement is carried out to obtain the smallest distance in moving raw materials in the production process. By rearranging the machine using the systematic layout planning method. The latest distance value was obtained at 60,865, which was originally 63,905. Therefore, making a machine layout can be done using the proposed layout.